Pengembangan Modul Pembelajaran Berbasis Web pada Mata Pelajaran Penerapan Rangkaian Elektronika - Irma Junita; Sukardi Sukardi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2020)
Student learning process activities must have teaching materials so that it can make it easier for students to understand the learning material. The learning module developed is in the form of online teaching materials or in electronic form. The development of learning modules is carried out to produce valid and practical learning modules. The module being developed is a learning module on the Application of Electronic Compounds for class XI TAV which is Web-based. The research was conducted at SMKN 1 Koto XI Tarusan which does not yet have teaching materials in the electronic form to help students learn independently. The development of the learning module for the application of electronic circuits was developed using a 4-D development model. The research method, namely R&D (Research & Development) in the development procedure using 4-D, there are four stages, namely the first stage of defining, the second stage of design, the third stage of development (develop), and dissemination (disseminate). Data were collected using a Likert scale questionnaire with data analysis techniques using percentage techniques. Based on the research results, the validity value was obtained in the valid category. Practicality tests with teacher respondents were obtained in the very practical category and practicality tests with student respondents were obtained in a very practical category.